Abdominal wall muscle elasticity and abdomen local stiffness on healthy volunteers during various physiological activities. (July 2016) - Tran, D.; Podwojewski, F.; Beillas, P.; Ottenio, M.; Voirin, D.; Turquier, F.; Mitton, D.
Abstract: The performance of hernia treatment could benefit from more extensive knowledge of the mechanical behavior of the abdominal wall in a healthy state. To supply this knowledge, the antero-lateral abdominal wall was characterized in vivo on 11 healthy volunteers during 4 activities: rest, pullback loading, abdominal breathing and the "Valsalva maneuver". The elasticity of the abdominal muscles (rectus abdominis, obliquus externus, obliquus internus and transversus abdominis) was assessed using ultrasound shear wave elastography. In addition, the abdomen was subjected to a low external load at three locations: on the midline (linea alba), on the rectus abdominis region and on lateral muscles region in order to evaluate the local stiffness of the abdomen, at rest and during "Valsalva maneuver". The results showed that the "Valsalva maneuver" leads to a statistically significant increase of the muscle shear modulus compared to the other activities. This study also showed that the local stiffness of the abdomen was related to the activity. At rest, a significant difference has been observed between the anterior (0.5 N/mm) and the lateral abdomen locations (1 N/mm). Then, during the Valsalva maneuver, the local stiffness values were similar for all locations (ranging from 1.6 to 2.2 N/mm). This work focuses on the in vivo characterization of the mechanical response of the human abdominal wall and abdomen during several activities. In the future, this protocol could be helpful for investigation on herniated patients. Graphical abstract: Highlights: In vivo abdominal wall elasticity during various physiological loadings. Shear elasticity of the abdominal muscles is significantly affected by the Valsalva maneuver. Abdominal muscle elasticity can be assessed in vivo using an non-invasive technique.